Fibrillins in Tendon - Giusti, Betti; Pepe, Guglielmina (Frontiers in Aging Neuroscience, 2016)
Tendons among connective tissue, mainly collagen, contain also elastic fibers (EF) made of fibrillin 1, fibrillin 2 and elastin that are broadly distributed in tendons and represent 1–2% of the dried mass of the tendon. Only in the last years, studies on structure and function of EF in tendons have been performed. Aim of this review is to revise data on the organization of EF in tendons, in particular fibrillin structure and function, and on the clinical manifestations associated to alterations of EF in tendons. Indeed, microfibrils may contribute to tendon mechanics; therefore, their alterations may cause joint hypermobility and contractures which have been found to be clinical features in patients with Marfan syndrome (MFS) and Beals syndrome. The two diseases are caused by mutations in genes FBN1 and FBN2 encoding fibrillin 1 and fibrillin 2, respectively.